The RELATIONSHIP OF MOTIVATION, COMMITMENT AND WORK DISCIPLINE TO EMPLOYEES PERFORMANCE IN GENERAL HOSPITALS INDONESIAN CHRISTIAN UNIVERSITY - Hosiana, Debora; Tampubolon, Emma; Tobing, Fenny B.N.L (Universitas Kristen Indonesia, 2018)
Human resources owned by the company must have the ability to run a business, given the factors of service provided by these employees greatly determine the of the company in the future. The ability that have been possessed must continue to be honed continuously through work experience, training, competence, discipline, work motivation was to determine the relationship of motivation, commitment and work discipline to employee performance at the Indonesian Christian University General Hospital. This research is descriptive-quantitative with a sample population of 99 employees and correlations Rank Spearmaking and Hypothesis Test. That (1) motivation for the performance of employees of the Indonesian Christian University General Hospital. This is shown by obtaining tcount (5,107) greater than t table (1,661). (2) commitment to the performance of employees of the Indonesian Christian University General Hospital. This is indicated by the obtained tcount (6,805) greater than t table (1,661). (3) to work discipline with the performance of employees of the General University of Indonesia Christian Hospital. This is indicated by the obtained tcount (6.929) greater than t table (1.661). Based on study, it can be concluded that if motivation, commitment and work discipline are carried out properly, it performance of the Indonesian Christian University General Hospital, but it needs to be addressed and improved such as giving more motivation so that employees are more active in working so that the level of in accordance with the goals and company expectations. Keywords: motivation, commitment, work discipline and performance